An isolated case of pseudothrombocytopenia due to platelet satellitism with the review of literature - Meenakshi Suri (Annals of Medical Science and Research)
Platelet interaction with neutrophil polymorphs happens rarely, forming platelet aggregates like rosettes/beads around neutrophils, an uncommon phenomenon called ‘platelet satellitism’ (PS). It has been observed in peripheral blood smears prepared from blood samples anticoagulated with ethylene diamine tetra-acetic acid, but not in blood samples treated with heparin or sodium citrate. Automated hematology analyzers in present times have increased the reproducibility and accuracy of platelet counts, they may not completely resolve pseudothrombocytopenia. Being a rare cause of spurious thrombocytopenia, it might mislead the clinician into unnecessary investigations and treatment. To avoid false reporting of low platelet count, the peripheral blood smear examination should be performed in all patients with thrombocytopenia. PS usually occurs around neutrophil granulocytes and only in extremely rare cases are platelets phagocytosed by neutrophils, forming rosettes around lymphocytes and monocytes as observed only in patients with neoplastic lymphocytes. This study presents an isolated case of spurious thrombocytopenia due to PS around neutrophils, with platelet phagocytosis.